The variability of pollution load of organic, biogenic and chromium ions in wastewater inflow to the treatment plant in Nowy Targ - Bugajski Piotr M.; Nowobilska-Majewska Elwira; Kurek Karolina (Journal of Water and Land Development, 2017)
The aim of the study was to analyze the mean daily wastewater load from the corporate wastewater treatment plant in Nowy Targ. The study analyzed the wastewater load expressed by BOD5, COD, total nitrogen (Ntot), total phosphorus (Ptot) and chromium ions (Cr). The study was conducted from 2006 to 2016, in which 591 samples of raw wastewater were collected and analyzed in a control well before the treatment plant with a mean of 4 times a month. The scope of research in the analytical part covered the variability of wastewater loads in individual years and determined the characteristic values of mean daily load in particular months. Mean daily wastewater load for BOD5 – 7 053 kg·d−1 for COD – 23 437 kg·d−1 for total nitrogen – 1 464 kg·d−1 for total phosphorus – 197 kg·d−1 and for chromium ions – 129 kg·d−1. For each of the analyzed index, it was found that in the each months mean daily wastewater load in raw wastewater is variable. In the analyzed period the mean daily discharged wastewater oscillated within 13 924 m3·d−1, which accounted for about 66% of the projected load.